A new rock dwelling Hemidactylus (Squamata: Gekkonidae) from Chhattisgarh, India - Murthy, B.h.c.k.; Bauer, Aaron; Lajmi, Aparna; Agarwal, Ishan; Giri, Varad B. (Zootaxa, 2015)
A distinct new species of gecko of the genus Hemidactylus is described from the Kanker district of Chhattisgarh State, east-central India. This large-sized (SVL average 81.33±13.40 to at least 98.0 mm) Hemidactylus is characterized by a dorsum with small granules, intermixed with 10–12 rows of irregularly arranged, slightly larger, rounded, weakly-keeled tubercles at midbody; 10–12 and 13–15 subdigital lamellae on the first and fourth digits, respectively, of both manus and pes; a single enlarged postcloacal tubercle on either side of the tail; 10–12 femoral pores on each thigh separated by 5–8 poreless scales; 12–14 supralabials and 10–12 infralabials.